Investigation on polyaniline enriched tin cerium phosphate thermally stable fibrous composite ion exchanger for environmental remediation - C., Janardanan; Valsaraj P, Vinisha (International Journal of Advanced Chemistry, 2014)
Abstract: We fabricate a novel ion exchanger of tin cerium phosphate, by incorporation of polyaniline conducting polymer by ex-situ polymerization method, as a potential candidate for environmental remediation based on the concept of composite material. The study showed its utility as ion exchanger in the separation chemistry. SEM image of composite showed its fiber like morphology. The distribution coefficient studies showed its selectivity towards Pb (II) and Bi (III) metal ions. The adsorption isotherm and kinetic study of dye adsorption on this material was carried out. This study implies that this hybrid material can be suggested as eco-friendly material for the environmental monitoring. Keywords: Adsorption, composite, ion exchanger, organic dye, polyaniline.